2017
DOI: 10.1016/j.jacc.2017.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Incident Myocardial Infarction and Very Late Stent Thrombosis in Outpatients With Stable Coronary Artery Disease

Abstract: In stable CAD outpatients, incident MI occurs at a stable rate of 0.8% annually, is related to VLST in one-fifth of cases, and is associated with an increased mortality risk, especially for VLST. Multivessel CAD and residual uncontrolled risk factors are strongly associated with MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 32 publications
0
25
0
2
Order By: Relevance
“…However, recent studies have shown that the annual mortality rate of SCAD is 0.63–3.8% . The CORONOR study showed that the annual incidence of myocardial infarction was 0.8% for patients with SCAD. Therefore, it is important to identify high‐risk patients with SCAD.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that the annual mortality rate of SCAD is 0.63–3.8% . The CORONOR study showed that the annual incidence of myocardial infarction was 0.8% for patients with SCAD. Therefore, it is important to identify high‐risk patients with SCAD.…”
Section: Introductionmentioning
confidence: 99%
“…These patients should be initiated on pathways to improve their lifestyles and especially on pathways that favor the cessation of cigarette smoking. In a systematic review of the scientific literature on lifestyle changes in patients with chronic ischemic heart disease, it has been found that the cessation of smoking, introduction of a healthier diet and engagement in physical activity may lead to a 36%, 44%, and 24% reduction in mortality, respectively . Recently, it has been found that in obese patients without metabolic alterations, the incidence of coronary heart disease is 49% higher than in non‐obese patients .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, patients with cardiovascular disease may incorrectly self‐report smoking status since they are under the pressure to quit smoking 38. For CABG, several trials have shown its survival benefits compared with percutaneous revascularization or medical treatments in patients with severe coronary heart disease 39, 40, 41. Thus, the prognostic value of CABG may depend on patient characteristics.…”
Section: Discussionmentioning
confidence: 99%